PENDAMPINGAN PEMASARAN PRODUK DAN PELATIHAN PENYUSUNAN PEMBUKUAN PADA UMKM KERAJINAN BATOK KEPALA DI DESA TIMPAG KERAMBITAN TABANAN - Kadek Dewi Padnyawati; Ni Putu Ayu Kusumawati; Mirah Ayu Putri Trarintya; Ni Made Wisni Arie Pramukiwisn; Ni Wayan Alit Erlinawati; Cokorda Gde Bayu Putra (JURNAL SEWAKA BHAKTI, 2021)
Most of the people in Timpag Village, Kerambitan District, Tabanan, rely on agriculture, plantations and livestock. The majority of plantation products in Timpag Village are head producers. The community in Timpag Village processes coconut into various kinds of preparations such as food and crafts. MSME coconut shell crafts Mr. Si Made Merta has been running for 7 years by processing coconut shells into extraordinary handicrafts such as soap holders, ashtrays, buckles, incense holders and other shell crafts with various unique and interesting shapes. The problem faced by MSME Mr. Si Made Merta in running his business is a lack of understanding of marketing and preparation of financial reports so that the business he is running has not been able to develop properly. Marketing techniques have a very important role in running a business because customer satisfaction is the final goal in marketing techniques, it is necessary to understand and understand proper marketing management. Financial reporting in a business is the final process of the accounting process. This report serves as information material and decision-making material for users in running their business. Based on these problems, we provide assistance and training in simple Marketing Techniques and Financial Statement Preparation Training so that in the future the business can be more advanced and compete in the midst of the current rapid economic growth. With this community service, it is hoped that MSMEs Mr. Si Made Merta will be able to carry out marketing techniques properly and also in preparing correct financial reports.